Based Image Watermarking Algorithm Based on Qr Decomposition in Lifting Wavelet - Kumar Shrivastava, Shailesh; S.K Mahendran ting Wavelet, Dr. (International Journal of Engineering and Technology, 2018)
In this paper, a non-blind watermarking system based on lifting wavelet transform and QR factorization has been proposed. The variance between coefficients of lifting wavelet transform in a block of size 2 x 2 has been used to embed binary watermark and blocks are randomly shuffled. The system minimizes distortion of watermarked image. The performance of scheme has been tested on some standard images and the simulation results have been evaluated and compared with some traditional methods. The experimental result shows that the proposed system is robust against image processing attacks.